2016
DOI: 10.1007/s00436-016-5129-8
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and differential expression analysis of Toxocara canis aquaporin-1 gene

Abstract: Toxocara canis is an intestinal nematode of canids with a worldwide distribution, causing an important but neglected parasitic zoonosis in humans. Aquaporins (AQP) are a family of water channel proteins, which function as membrane channels to regulate water homeostasis. In this study, the coding sequence of aquaporin-1 gene of T. canis (Tc-aqp-1) was cloned and characterized. The obtained Tc-aqp-1 coding sequence was 933 bp in length, which predicted to encode 311 amino acids. Two conserved asparagine-proline-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Although nematodes do not have tegument, which have evolved to possess the specialised coat (cuticle), the functional roles of intestinal AQPs in nematodes should be similar to the tegument AQPs in trematodes as both of them are important organs known for nutrient absorption. This proposal can be somewhat supported by the predominant gene transcription of Tc-aqp-1 and protein expression of Tc AQP1 in the intestine of adult T. canis [30]. Interestingly, Tc AQP1 was localised specifically on the intestinal basolateral membrane, which is consistent with the tissue expression of AQP1 in C. elegans [4].…”
Section: Discussionmentioning
confidence: 71%
See 4 more Smart Citations
“…Although nematodes do not have tegument, which have evolved to possess the specialised coat (cuticle), the functional roles of intestinal AQPs in nematodes should be similar to the tegument AQPs in trematodes as both of them are important organs known for nutrient absorption. This proposal can be somewhat supported by the predominant gene transcription of Tc-aqp-1 and protein expression of Tc AQP1 in the intestine of adult T. canis [30]. Interestingly, Tc AQP1 was localised specifically on the intestinal basolateral membrane, which is consistent with the tissue expression of AQP1 in C. elegans [4].…”
Section: Discussionmentioning
confidence: 71%
“…Recent genomic and transcriptomic studies on this parasite have indicated that Tc-aqp-1 might play important roles in the host-parasite interactions [4446]. In our recent work [30], we have revealed the transcription profile of Tc-aqp-1 in the different tissues of adult T. canis . As a logical extension, in this study, we explore the tissue expression and function of Tc AQP1 protein in the adult (female and male) worms of T. canis , using immunohistochemistry, RNA interference and nematocidal assays.…”
Section: Introductionmentioning
confidence: 84%
See 3 more Smart Citations